(untitled) (Comprehensive Journal of Science, 2026)
This study examines the phenomenon of vowel alteration (iʿlāl) in Surat Al-Zukhruf, considering it one of the prominent phonological and morphological features of the Arabic language. This phenomenon manifests through systematic modifications of weak letters—namely substitution, deletion, and transposition—governed by established phonological and morphological rules and recurrent patterns. Such processes reflect the flexibility of Arabic morphological structure and highlight the aesthetic qualities of the linguistic system in achieving both rhythmic and semantic harmony. The study adopts a descriptive-analytical approach, which is well suited to the objectives of the research. Instances of vowel alteration were identified, classified, and analyzed according to their specific morphological forms, enabling the detection of underlying patterns and the elucidation of their role in shaping the phonological and morphological structure of the Qur’anic text. The research is guided by several key questions, most notably: What types of vowel alteration occur in the words of Surat Al-Zukhruf, and which of these types are most prevalent within its verses? The findings reveal that vowel alteration occurs in thirty-five verses of Surat Al-Zukhruf, with substitution appearing in fifteen verses, deletion in twenty-two verses, and transposition in four verses. These results underscore the aesthetic and semantic significance of vowel alteration, as it contributes to rhythmic coherence, facilitates ease of articulation in Arabic words, and reflects the adaptability of the Arabic morphological system to phonological and contextual demands. Accordingly, the study demonstrates that examining vowel alteration in Surat Al-Zukhruf sheds light on an aspect of the Qur’an’s linguistic inimitability, wherein form and meaning converge within a unique linguistic framework that combines morphological precision with phonetic elegance.